1999
DOI: 10.1007/s002449900441
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA Strand Breaks and Expression of HSP70 and GRP78 Homolog by Cadmium in the Marine Sponge Suberites domuncula

Abstract: The marine sponge Suberites domuncula was used as a bioindicator to study the effects of cadmium on the occurrence of DNA strand breakage and on the induction of the expression of the stress biomarkers, heat shock protein 70 (HSP70) and glucose-regulated protein 78 (GRP78) homolog. The cDNA encoding GRP78 homolog from S. domuncula was isolated and characterized. The GRP78 cDNA has a length of 2.1 kb and displays characteristic features of the HSP70 family; it encodes an aa sequence of Mr 72,000. Exposure of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…A similar phenomenon has also been reported in Aurelia spp. (Schroth et al 2005) and in sponges exposed to cadmium (Schröder et al 1999). The 31°C treatment is much less acute but appears to cause some 103 Mar Ecol Prog Ser 431: 97-105, 2011 sub-lethal molecular responses that are able to return to normal once the thermal stress has been removed.…”
mentioning
confidence: 99%
“…A similar phenomenon has also been reported in Aurelia spp. (Schroth et al 2005) and in sponges exposed to cadmium (Schröder et al 1999). The 31°C treatment is much less acute but appears to cause some 103 Mar Ecol Prog Ser 431: 97-105, 2011 sub-lethal molecular responses that are able to return to normal once the thermal stress has been removed.…”
mentioning
confidence: 99%
“…The increased expression of hsps (hsp70, hsp60, and hsp27) in response to cadmium was demonstrated in tissues and cells of many organisms, e.g., sponges [5], Drosophila [7], nematodes [8,9], and human cells [10].…”
mentioning
confidence: 99%
“…The metal is highly dangerous not only because it easily penetrates the cells but also because it is eliminated very slowly (Jarup et al 1998). In the majority of cases, it damages chromosomes and inhibits the mechanisms implicated in DNA repair (Schroder et al 1999). It is known that heavy metals interfere on gametogenesis, inhibit embryogenesis, and interrupt development at different stages (Au et al 2001;Fernandez and Beiras 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that heavy metals interfere on gametogenesis, inhibit embryogenesis, and interrupt development at different stages (Au et al 2001;Fernandez and Beiras 2001). Cadmium exposure can also induce apoptosis in testicular tissue of rat, mouse liver, human T-cells (Xu et al 1996;Habeebu et al 1998;Tsangaris and Tzortzatou-Stathopoulou 1998), and marine sponges (Schroder et al 1999); on the other hand, it has been demonstrated that caspase inhibitors attenuated Cd-induced apoptosis (Galan et al 2000). In response to different stresses, the cells activate the synthesis of heat shock proteins (Hsps), caused by the accumulation of denatured proteins.…”
Section: Introductionmentioning
confidence: 99%